2022
DOI: 10.3390/su14084719
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Development of the CNN Model Considering Teleconnection for Spatial Downscaling of Precipitation in a Climate Change Scenario

Abstract: Global climate models (GCMs) are used to analyze future climate change. However, the observed data of a specified region may differ significantly from the model since the GCM data are simulated on a global scale. To solve this problem, previous studies have used downscaling methods such as quantile mapping (QM) to correct bias in GCM precipitation. However, this method cannot be considered when certain variables affect the observation data. Therefore, the aim of this study is to propose a novel method that use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Nourani et al (2019) also used a larger geographic area for predictors than the geographic extent of the predictand to maximise spatial learning and potentially boost downscaling performance. This idea was tested more thoroughly by Kim et al (2022) where they identified most relevant regions for plausible teleconnections (climatic influences from remote regions) and included them into their training dataset. More recent studies have tested convolutional neural networks (CNNs) that rely on spatial learning and can read climatic data in form of 2D images (Vandal et al, 2019;Liu et al, 2020;Baño-Medina et al, 2021;Damiani et al, 2024) for climate downscaling.…”
Section: Introductionmentioning
confidence: 99%
“…Nourani et al (2019) also used a larger geographic area for predictors than the geographic extent of the predictand to maximise spatial learning and potentially boost downscaling performance. This idea was tested more thoroughly by Kim et al (2022) where they identified most relevant regions for plausible teleconnections (climatic influences from remote regions) and included them into their training dataset. More recent studies have tested convolutional neural networks (CNNs) that rely on spatial learning and can read climatic data in form of 2D images (Vandal et al, 2019;Liu et al, 2020;Baño-Medina et al, 2021;Damiani et al, 2024) for climate downscaling.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, satellite products with a high temporal resolution are often required to be spatially downscaled (disaggregation of a coarse cell into many finer cells) for various environmental applications. In the past 10 years, numerous spatial downscaling studies have been conducted on many satellite-derived products, such as precipitation [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], soil moisture [15], [16], [17], [18], [19], [20], [21], [22], [23], land surface temperature [2], [24], [25], [26], [27], [28], [29], [30], night-time light [31], solar radiation [32], evapotranspiration [33], [34], [35], chlorophyll [36], and wind speed [37]. The primary goal of spatial downscaling research is to improve the downscaling performance of satellite-derived products which is generally performed from two main aspects [38]: the introduction of new auxiliary variables [5], [8], [39], [40] and the development of new downscaling models [6], [13], [22],…”
Section: Introductionmentioning
confidence: 99%
“…So far, many algorithms have been developed for HCD [20]. It is widely reported that Deep Learning (DL) algorithms have the highest accuracies [21][22][23]. A DL approach can automate the learning of features on input data at several abstraction levels [24,25].…”
Section: Introductionmentioning
confidence: 99%